Productivity formation of sunflower hybrids with the use of plant growth regulators - V. М. SENDETSKYI; І. А. SHUVAR; Т. V. MELNYCHUK; О. Ya. CHERNYSHENKO; T. V. SHEVCHENKO (Передгірне та гірське землеробство і тваринництво, 2022)
Sunflower is the main oil crop in Ukraine, which provides almost 90 % of oil production, the volume of which increases annually, mainly due to the expansion of cultivated areas. Crop yield during 2013‒2017 was 1.9‒2.2 t/ha for varieties suitable for distribution in Ukraine included in the State Register of Plants suitable for distribution in Ukraine with a productivity of 3.5‒5.0 t/ha. Therefore, it is actually to search for reserves to further increase the yield of crops under the conditions of global climate change, improve the quality of products and reduce the negative impact on soil fertility and the surrounding natural environment. The solution to this problem is possible by improving the elements of sunflower cultivation technology, including the use of plant growth regulators.